CURRENT PROCEDURAL ASSESSMENTS OF THE EUROPEAN UNION COURT OF JUSTICE REGARDING INTERNATIONAL JURISDICTION IN VIOLATIONS OF PERSONALITY RIGHTS OCCURING ON THE INTERNET - TEKİN, Esra (SSD Journal, 2021)
Rapid developments in information and communication technologies have brought up legal problems that need to be solved. In particular, the fact that the internet has made geographical borders unimportant has made the violations of personality rights widespread. It is important in terms of international procedural law from which court the legal claims regarding these violations containing a foreign element will be requested. As a matter of fact, it is very difficult to localise the violation to a geographical area in the internet environment. The Brussels Ibis Regulation on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters provides harmonization regarding procedural matters in the member states of the European Union. Since the violations of personality rights that occur on the Internet are classified as torts, the international jurisdiction of the courts is determined according to Article 7(2) of the Regulation. While this provision, which gives competence to the courts of the place where the damage has occurred or may occur, is applied to the violations of personality rights on the internet, the member states have requested a preliminary ruling from the Court of Justice of the European Union. In 2011, the CJEU brought the expression “the place where the alleged victim has his/her centre of interests”, which is a new jurisdiction ground to the legal literature. In our study, especially the Mitterbayerischer decision, which is the latest decision on the subject, and the previous CJEU decisions, will include explanations on the determination of international jurisdiction in violations of personality rights on the internet.